2013
DOI: 10.1111/j.1945-1474.2011.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Failures in Transition: Learning from Incidents Relating to Clinical Handover in Acute Care

Abstract: The appropriate handover of patients, whereby responsibility and accountability of care is transferred between healthcare providers, is a critical component of quality healthcare delivery. This paper examines data from recent incidents relating to clinical handover in acute care settings, in order to provide a basis for the design and implementation of preventive and corrective strategies. A sample of incidents (n = 459) relating to clinical handover was extracted from an Australian health service's incident r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 24 publications
3
56
1
10
Order By: Relevance
“…Investigation of adverse consequences resulting from inadequate handover of care has shown that critical information about an individual patient's medical condition or care plan is frequently not conveyed to the new care provider. 3 Providing such information should not be an overwhelming obstacle for hospital pharmacists.…”
Section: Improving Handover Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of adverse consequences resulting from inadequate handover of care has shown that critical information about an individual patient's medical condition or care plan is frequently not conveyed to the new care provider. 3 Providing such information should not be an overwhelming obstacle for hospital pharmacists.…”
Section: Improving Handover Of Carementioning
confidence: 99%
“…One suggestion for improvement is establishing and enforcing a minimum standard for information that should be provided regarding the conditions and care plan of each patient. 3 The Scottish Intercollegiate Guideline Network has recently published a guideline outlining the information recommended for handover of care upon hospital discharge. 4 Canadian pharmacy investigators have proposed a tool with mandatory elements regarding the patient's drug therapy and unresolved drug-related issues.…”
Section: Improving Handover Of Carementioning
confidence: 99%
“…À la faveur de ces résultats, nous pourrions être portés à croire que les collègues dans nos établissements respectifs se réjouiraient ou exigeraient de recevoir de tels renseignements afin de prendre en charge les soins lors du transfert de patients d'un service hospitalier à l'autre ou lors du relais entre les quarts de travail, comme l'horaire de chacun ne permet pas une disponibilité en tout temps : aucun d'entre nous ne travaille 24 heures sur 24 et 7 jours sur 7 tout au long de l'année après tout! L'examen des conséquences indésirables découlant du mauvais transfert des soins a montré que des renseignements essentiels à propos de l'état du patient ou de son plan de soins ne sont souvent pas transmis au fournisseur de soins suivant 3 . Fournir ces renseignements ne devrait pas représenter une tâche insurmontable pour les pharmaciens hospitaliers.…”
unclassified
“…L'une des suggestions d'amélioration serait de mettre en place et de faire respecter une norme indiquant le minimum de renseignements sur l'état du patient et sur son plan de soins qui doivent être fournis au moment du transfert 3 . Récemment, le Scottish Intercollegiate Guideline Network a publié une ligne directrice définissant les renseignements qu'il est recommandé de fournir pour le transfert des soins au congé de l'hôpital 4 .…”
unclassified
“…Clinical environments are dynamic and complex, presenting many challenges for effective communication. The literature highlights the effects of ineffective handover such as wrong patients identification, wrong site surgery and, sometimes, patient death (Rabøl et al, ISSN 2377-3219 2017 2011; Thomas et al, 2013). The communication methods impact on the effectiveness and efficiency of handover as well as patient safety.…”
Section: Introductionmentioning
confidence: 99%